Illness perception in pediatric somatization and asthma: complaints and health locus of control beliefs - Bundschuh Silke; Goldbeck Lutz (BMC, 2007)
Abstract Background Health- and illness-related cognitions of pediatric patients with asthma or somatization and of their caregivers are considered relevant for patient education and for cognitive-behavioral interventions. This study investigates the relationship between diagnosis and illness perception by child and parent in two different chronic conditions such as somatization disorder and asthma. Methods 25 patients with somatoform disorders and 25 patients with asthma bronchiale completed the Giessen Complaint List and the Multidimensional Health Locus of Control Scale. Primary caregivers independently answered parallel proxy-report instruments. Analyses of variance were performed to determine the impact of diagnosis and perspective. Correlations were calculated to determine the concordance between patient and caregiver reports. Results No statistically significant differences in illness locus of control beliefs were found between asthma and somatoform disorder children or parents. Parents reported more internal and fatalistic locus of control beliefs compared with their children. Correlations between patient and caregiver reports of symptoms and health locus of control beliefs were low to moderate. Conclusion Clinicians should take into account a sense of insufficient symptom control in both diagnostic groups and different viewpoints of patients and their parents.